ASUHAN KEBIDANAN IBU HAMIL DENGAN PENGARUH SELF HYPNOSIS TERHADAP KUALITAS TIDUR IBU Y TRIMESTER III KECAMATAN MEUREBOH KABUPATEN ACEH BARAT - Sakila, Ajiera; Zahara, Evi; Asmanidar, Asmanidar; Yushida, Yushida (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Lack of sleep quality is one of the common forms of discomfort felt by pregnant women, especially those who have entered the third trimester of pregnancy. There are 66.7% of third trimester pregnant women who have poor sleep quality because they feel discomfort in their pregnancy. The impact of the lack of sleep quality in third trimester pregnant women affects the condition of the mother or baby during pregnancy or in childbirth later. Pregnant women with poor sleep quality can cause complications in pregnancy such as premature birth, increased maternal blood pressure and can make the labor process longer and at greater risk for cesarean section. In dealing with this, efforts can be made to handle non-pharmacological therapies such as self hypnosis. Self hypnosis is a technique to hypnotize oneself followed by the acceptance of a certain suggestion or thought. Objective: To analyze the effect of self hypnosis on sleep quality of third trimester pregnant women. Methods: Using a pre experimental one group pre test post test design which was carried out in March-April 2023 at TPMB Midwife Yulis Aktriani, S.Tr.Keb. The sampling technique was purposive sampling and used the Wilcoxon analysis test. Results: The results of the statistical analysis test using the Wilcoxon test with a p-value of 0,180 (>0,05) show that there is no significant effect between self hypnosis on the quality of sleep of pregnant women in the third trimester. Conclusion: There is no effect of self hypnosis on sleep quality of third trimester pregnant women